Plant growth promoting rhizobacteria as a biological tool for augmenting productivity and controlling disease in agriculturally important crop- A review - Dileep Kumar, B S; Jacob, J. (Journal of Spices and Aromatic Crops, 2020)
The ecological role of plant growth promoting bacteria associated with plant root environment is currently gaining increased attention. The tremendous use of chemical fertilizers and pesticides which are environmentally harmful can be replaced with these microbes generally called as Plant Growth Promoting Rhizobacteria (PGPR). These microbes can be developed as biofertilizers because they are eco-friendly, cost effective and are natural living organisms. The advantages of these microorganism rely on their production of novel bioactive metabolites that inhibit various pathogens in soil as well as their vast mechanisms in improving growth, productivity and yield in agriculturally important crops. Apart from this, their role in nutrient acquisition, soil fertility improvement and stress tolerance are also inevitable. This review represents the present scenario of beneficial bacteria as plant growth agents and disease control tools. They have been extensively studied for plant disease suppression, plant growth modulation, and interaction with plants. Here, some mechanisms employed by plant growth promoting bacteria from different environments are discussed.